Cost-effectiveness and potential budget impact of non-pharmacological interventions for early management in prehypertensive people: an economic evaluation for China - Leyi Liang; Taihang Shao; Hao Li; Mingye Zhao; Wenxi Tang (BMC, 2023)
Abstract Background Non-pharmacological interventions (NPIs) could be considered in the early management of prehypertensive population. This study aimed to evaluate the potential cost-effectiveness of NPIs and the budget impact of implementing NPIs on prehypertensive population in China and provide evidence of chronic disease management innovation for decision-makers. Methods Five NPIs including usual care, lifestyle, strengthen exercise, relaxation, and diet therapy were selected based on the practice of hypertension management in China. A nine-state Markov model was constructed to evaluate the lifetime costs and health outcomes of five NPIs and a non-intervention group from the perspective of Chinese healthcare system. The effectiveness of NPIs was obtained from a published study. Parameters including transition probabilities, costs and utilities were extracted or calculated from published literature and open-access databases. Sensitivity analyses were conducted to test the uncertainty of all parameters. The impact of duration of intervention was considered in scenario analyses. A budget impact analysis (BIA) was conducted to evaluate the total cost and the medical cost saving of a hypothetical nationwide implementation of potential cost-effective NPI in prehypertensive people. Management strategies including focusing on patients with specific ages or different CVE risk levels, and different duration of implementation were taken into consideration. Results Strengthen exercise was the most cost-effective intervention with a probability of 78.1% under the given WTP threshold. Our results were sensitive to the cost of interventions, and the utility of prehypertension and hypertension. The duration of implementation had limited impact on the results. BIA results showed that the program cost was hefty and far more than the medical cost saving with the course of simulation time. Applying management strategies which focused on individual characteristics could largely reduce the program cost despite it remained higher than medical cost saving. Conclusions Strengthen exercise was a potential NPI that can be considered in priority for early management in prehypertensive population. Although early management can acquire medical cost saving, the related program cost can be quite hefty. Precise strategies which may help reduce the cost of early management should be taken into consideration in program design.